Problematic Internet Usage Behaviours Of Undergraduate Students: A Modelling Study (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
This study aims to examine the problematic internet usage behaviours of undergraduate students through structural equation model. The research group of this study consists of 2026 undergraduate students enrolled in universities representing the seven geographical regions of Turkey. Universities were selected via stratified method and individuals from these universities were selected by random sampling during the 2014-2015 academic year. In order to collect data, the Problematic Internet Usage Behaviours Scale for Undergraduate Students, developed by the researchers, was used. The scale consists of 32 items and 9 factors, including demographic information. The results revealed that the factors affecting the problematic internet usage behaviours of the students were; social satisfaction, emotional satisfaction, internalization, perception of prestige, physical negative impact, overuse, loss of control, academic failure and internal deception. In addition, correlation of factors was modelled and evaluated. When the structured model was examined it was seen that, perception of prestige, internal deception and overuse did not affect the physical negative impact factor. In addition to this, it was determined that the emotional satisfaction factor did not affect the overuse factor. Apart from these examples, all the other factors affect each other at different levels.